CHANGES IN LANDSCAPE METRICS INDUCED BY DEFORESTATION IN ROSCI0358 PRICOP-HUTA-CERTEZE NATURE 2000 SITE - CORPADE, C.; BĂDĂRĂU, Al. S.; CORPADE, Ana-Maria; HOGNOGI, Gh.; POP, Simona; BANC, Ştefana (Studia Universitatis Babeș-Bolyai Geographia, 2016)
Changes in Landscape Metrics Induced by Deforestation in RoOSCI0358 Pricop-Huta-Certeze Nature 2000 Site. The paper analyzes the changes in the landscape structure within the territory of the Site of Community Interest ROSCI0358 Pricop-Huta-Certeze as a consequence of deforestation. Deforestations between 1972 and 2010 were analyzed and mapped. GIS instruments have been used in order to identify the changes in the spatial structure of landscape units induced by deforestation (changes in land parcels shape, number, edge etc.) by the help of some relevant landscape metrics indices. Results are discussed in relation to the protection status of the area (included in the Nature 2000 ecological network) and its conservation objectives.